Nanoparticles as Structure-Directing Agents for Controlling the Orientation of Block Copolymer Microdomain in Thin Films - Kim, Seyong; Wang, Hyun Suk; Jang, Se Gyu; Choi, Soo-Hyung; Kim, Bumjoon J.; Bang, Joona (WILEY-BLACKWELL, 2016)
Block copolymer/nanoparticle (BCP/NP) composites have attracted much attention due to their easiness of fabricating nanoscopic hierarchical structures, and significantly enhanced chemical and physical properties of the nanocomposites. Most of the focus in co-assembly of BCPs and NPs has been placed on the controlled alignment of NPs, "passively," in the BCP domain. However, NPs with carefully designed interfacial properties "actively" direct self-assembled structure of BCP in a nonconventional route. Herein, we review recent investigations of the self-assembly of BCP domains in thin films via the addition of structure-directing organic and inorganic NPs. Understanding the phase behavior of BCP/NP coassembly along with the theoretical description can shed a light on the far-reaching potentials to creating nonconventional nanostructures rarely obtained via traditional fabrication tools. (C) 2015 Wiley Periodicals, Inc.
Keywords: POLYMER-COATED NANOPARTICLES; HYBRID SOLAR-CELLS; GOLD NANOPARTICLES; INTERFACIAL INTERACTIONS; SURFACE NEUTRALIZATION; TRIBLOCK COPOLYMERS; OXIDE NANOPARTICLES; DIBLOCK COPOLYMERS; GLASS-TRANSITION; NANOCOMPOSITES